Calculation of atomic photoionization using the nonsingular convergent close-coupling method - Bray, A.; Kheifets, A.; Bray, Igor (American Physical Society, 2017)
The convergent close-coupling method for atomic photoionization is modified by treating the singularity in the Green's function analytically. The resultant close-coupling equations are then free of any singularities, and can be solved at all incident energies including at the exact thresholds. The utility and superiority of the approach is demonstrated by considering single photoionization of the ground state of helium at photoelectron energies from the ionic n=1,2,3 thresholds through to 1 keV. For completeness, the double photoionization cross section is also presented.